A mesoscale beam-spring combined mechanical model of needle-punched carbon/carbon composite. (10th November 2018) - Han, Meng; Zhou, Chuwei; Zhang, Haijun
Abstract: Needle-punched carbon/carbon composite (NP C/C) has high temperature resistance and reinforced interlaminar strength. Needle-punching technique improves the integrality of composite, nevertheless, it degrades the in-plane properties due to introducing a number of defects. In this study a mesoscale mechanical model was proposed, in which a kind of circular arc beam element (CABE) was established to characterize fiber bundle with punching defeats and extended spring elements (ESEs) were modeled to represent intralaminar and interlaminar bonds of fiber bundles. Uniaxial tension and compression experiments for a NP C/C were conducted to validate the proposed numerical model and good agreement was found between model predictions and test data.